History and Theory of Development Sociology - Akdila Bulanov; Syifa Aliya Zahra; Zulva Hamdi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Development sociology is a branch of sociology that specifically examines the processes of social, economic, and cultural change in the context of community development. This article traces the chronological history of development sociology, from its emergence after World War II to its dynamics in the contemporary era. Through a historical approach and theoretical analysis, this study identifies critical phases in the development of development sociology, including the emergence of modernization theory in the 1950s and 1960s, the critique of dependency theory in the 1970s, and the emergence of the sustainable development paradigm at the end of the 20th century. The results of this study indicate that effective development sociology focuses not only on economic growth but also includes dimensions of social justice, community participation, and environmental sustainability. By understanding its historical trajectory, development sociology can become a relevant analytical instrument in responding to global and local development challenges in the 21st century.